Conjoint Analysis and Design of Business and IT: The Case for Multi-Perspective Enterprise Modeling - Frank, U.; Bock, A. (Advanced Digital Architectures for Model-Driven Adaptive Enterprises, 2020)
This chapter presents a method for multi-perspective enterprise modeling (MEMO). Enterprise modeling fundamentally aims to support the conjoint analysis of business and IT to foster their integration. MEMO expands on this general aim with a specific concern for the professional perspectives of different stakeholder groups. MEMO is based on a language architecture that comprises an extensible set of domain-specific modeling languages, each addressing one or more professional perspectives. It is supplemented by an adaptable generic framework to support high-level ‘ballpark' views of an enterprise and to serve as a common starting point for more elaborate analysis and design tasks. MEMO also supports the construction of corresponding process models to design customized modeling methods. The chapter motivates the use of MEMO and illustrates possible use cases. It also provides a description of the method's architecture, its DSMLs, and a tool environment that supports the development and analysis of enterprise models.